THE USE OF ASSISTIVE DEVICES FOR PERSONS WITH DISABILITIES IN SOCIAL REHABILITATION CENTER WITH PHYSICAL DISABILITIES (BRSPDF) WIRAJAYA - Soetji Andari (Media Informasi Penelitian Kesejahteraan Sosial, 2020)
Abstrak Penggunaan alat bantu bagi Penyandang disabilitas sangat penting untuk melakukan aktifitas sehari-hari. Penelitian ini untuk mengetahui penyandang disabilitas dalam memanfaatan alat bantu di Balai Rehabilitasi Sosial Penyandang Disabilitas Fisik (BRSPDF) Wirajaya. Sasaran penelitian  dilakukan terhadap 60 orang penyandang disabilitas dan merupakan responden. Responden sebagian besar laki-laki 61.67 % dengan rentang usia mereka cukup variatif dan tergolong remaja dan dewasa, berpendidikan SMA/sederajat tidak memiliki pekerjaan, dengan status perkawinan, 100 % belum kawin.  Pemberian alat bantu untuk layanan disabilitas fisik di Balai Rehabilitasi Sosial Penyandang Disabilitas Fisik (BRSPDF) Wirajaya perlu mempertimbangkan estetika responden dengan kondisi (postur tubuh). Pelaksanaan pemberian alat bantu hendaknya mengacu pada SOP yang disesuaikan dengan UU dan Perda yang ada di wilayah masing-masing. BBRVBD diharapkan dapat bekerjasama dengan psikolog untuk mengetahui dan memotivasi responden dalam menerima keterbatasannya dan mendorong responden lebih percaya diri dalam menjalani hidup.Kata Kunci: Alat bantú; Disabilitas; Pemanfaatan; Rehabilitasi. AbstractThe use of assistive devices for persons with disabilities is very important to carry out daily activities. This study was to identify persons with disabilities in using assistive devices at the Wirajaya Social Rehabilitation Center for Persons with Disabilities (BRSPDF). The research target was carried out on 60 people with disabilities and who were beneficiaries. Most of the respondents were male, 61.67%, with a fairly varied age range and classified as adolescents and adults, high school education / equivalent, do not have a job, with marital status, 100% are not yet married. The provision of assistive devices for physical and sensory deaf speech disability services at the Wirajaya Social Rehabilitation Center for Persons with Disabilities (BRSPDF) needs to consider the aesthetics of the beneficiaries with their condition (body posture). The implementation of the provision of tools should refer to the SOP which is adjusted to the existing laws and regulations in each region. The Rehabilitation Center is expected to collaborate with psychologists to identify and motivate beneficiaries to accept their limitations and encourage beneficiaries to be more confident in living their lives.Keywords: Device ; Disabilities; Utilization; Rehabilitation